TERM RAHMAH DALAM AL-QUR’AN: (Studi Interpretasi Quraish Shihab dalam Tafsir Al-Misbah) - Hidayatullah, Alif Hendra (QOF, 2019)
Rahmah is a thematic study that has not been maximally touched by Muslims, especially Muslim scholars who specifically pursue the field of interpretation, because the interpretation and understanding of this Rahmah is considered final, but actually if it’s trace in either through a specific interpretation of the study or examining the books of Ulama interpretation which is Mu’tabar, certainly will find many kinds of meanings and interpretations of this Rahmah. In this studies the Rahmah was examined and presented through the perspective by Mufassir of Al-Qur’an namely Quraish Shihab in Tafsir al-Misbah, the point of this research have meaning that is Quraish Shihab interprets about Rahmah is not only to merciful and repayment of Allah in the form of heaven and others, it’s also means something that important in Allah creation as heaven but Rahmah is the inherent characteristic of the giver god who is not limited to something.